Banda - Short, Philip (London ; Boston : Routledge & Kegan Paul, 1974)
Biographical study of hastings kamazu banda and his political leadership of Malawi - includes information on his educational level, his career as a physician, the evolution of his political ideology and foreign policy, his role in gaining the country's independence, his attitude towards apartheid, international relations with South Africa R, etc. Bibliography pp. 317 to 320 and references. Biography banda h.k.
Includes bibliographical references (pages 317-320) and index.
Keywords: Banda, H. Kamuzu -- -1997.; Banda -- Hastings Kamuzu; Banda, H. Kamuzu -- -1997; Banda, Hastings Kamuzu -- 1898-1997; Banda, H. Kamuzu -- -1997.; Banda, Hastings Kamuzu, -- ca1906-1997.; Banda, Hastings Kamuzu, -- (1905-1997); Banda, Hastings Kamuzu; Presidents -- Malawi -- Biography; z; Malawi; politicians; biographies (form); Presidents; Politics and government; Dekolonisatie; Politici; Presidenten; political leadership; educational level; physician; political ideology; foreign policy; independence; attitude; apartheid; international relations; z; direction politique; niveau d'enseignement.; 2; 2; 2; 2; attitude; apartheid; relations internationales; 2; nivel educativo; 2; 2; 2; independencia; actitud; apartheid; relaciones internacionales; Malawi -- Politics and government; Malawi; Malawi -- Politique et gouvernement; Malawi; Malawi; South Africa; Malawi -- Politics and government; Malawi -- Politique et gouvernement -- 1964-1994.; Malawi; Afrique du Sud; 2; Malawi; Biographies; Malawi. Banda, Hastings